Akkermansia muciniphila improves metabolic profiles by reducing inflammation in chow diet-fed mice. (January 2017) - Zhao, Shaoqian; Liu, Wen; Wang, Jiqiu; Shi, Juan; Sun, Yingkai; Wang, Weiqing; Ning, Guang; Liu, Ruixin; Hong, Jie
Abstract : Abnormal shifts in the composition of gut microbiota contribute to the pathogenesis of metabolic diseases, including obesity and type 2 diabetes (T2DM). The crosstalk between gut microbes and the host affects the inflammatory status and glucose tolerance of the individuals, but the underlying mechanisms have not been elucidated completely. In this study, we treated the lean chow diet-fed mice with Akkermansia muciniphila, which is thought to be inversely correlated with inflammation status and body weight in rodents and humans, and we found that A. muciniphila supplementation by daily gavage for five weeks significantly alleviated body weight gain and reduced fat mass. Glucose tolerance and insulin sensitivity were also improved by A. muciniphila supplementation compared with the vehicle. Furthermore, A. muciniphila supplementation reduced gene expression related to fatty acid synthesis and transport in liver and muscle; meanwhile, endoplasmic reticulum (ER) stress in liver and muscle was also alleviated by A. muciniphila. More importantly, A. muciniphila supplementation reduced chronic low-grade inflammation, as reflected by decreased plasma levels of lipopolysaccharide (LPS)-binding protein (LBP) and leptin, as well as inactivated LPS/LBP downstream signaling (e.g. decreased phospho-JNK and increased IKBA expression) in liver and muscle. Moreover, metabolomics profiling in plasma also revealed an increase in anti-inflammatory factors such as α-tocopherol, β-sitosterol and a decrease of representative amino acids. In summary, our study demonstrated that A. muciniphila supplementation relieved metabolic inflammation, providing underlying mechanisms for the interaction of A. muciniphila and host health, pointing to possibilities for metabolic benefits using specific probiotics supplementation in metabolic healthy individuals.